Asuhan Keperawatan Anak Pada Pasien dengan Demam Tifoid Di Ruang Marwa Rumah Sakit ‘Asyiyah Pariaman Tahun 2026 - Arafatil Huda; Prima Yoselina; Reska Handayani; Yessy Aprihatin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Typhoid fever is an infectious disease of the small intestine caused by the bacteria Salmonella typhi characterized by increasing fever, decreased appetite, and digestive disorders, especially in pediatric patients. This study aims to provide pediatric nursing care to patients with typhoid fever using a case study method with a nursing care approach that includes assessment, diagnosis, intervention, implementation, and evaluation with data collection through interviews, observation, physical examination, and documentation. The author conducted the study from February 11 to 14, 2026 with the subject of the study, namely An.K with a medical diagnosis of typhoid fever who was treated in the Marwa Room of Aisyiyah Pariaman Hospital. The results of the study obtained nursing problems namely hyperthermia, nutritional deficit, ineffective airway clearance, and constipation. After being given nursing interventions for 4 days in the form of airway management, hyperthermia management, nutritional management, and elimination management the patient's condition improved marked by decreased fever, improved appetite, improved intestinal peristalsis, while the problem of airway clearance had not been completely resolved but had shown an improvement in clinical conditions, so that nursing care was effective in improving the patient's condition. It is hoped that patients and their families can provide care and maintain the cleanliness of each family member to avoid disease.